Evaluation of the Feasibility and Usefulness of the LMS Acceptance Questionnaire: Technology Confirmation During the Covid-19 Pandemic in Medical Students Users in Iran - Leili Mosalanejad; Sara Maghsodzadeh (Kerman University of Medical Sciences, 2022)
Background: Technology acceptance comprises cognitive and psychological elements about using technology.Objectives: This descriptive study evaluated the feasibility and applicability of the LMS acceptance questionnaire in medical sciences students using native LMS during the COVID-19 pandemic.Methods: This study was conducted to assess LMS acceptance and the validity of the questionnaires in Iranian society. Ten faculty members and ten students reviewed and evaluated the questionnaires for the validity of translation (content validity). Exploratory and confirmatory factor analysis methods were used for questionnaire items to determine the constructive validity. Moreover, a technology acceptance questionnaire was distributed among 200 users to determine the convergence validity. Finally, the reliability of the questionnaire was assessed by 30 people before, after, and simultaneously.Results: The results of this descriptive study showed that the average scores of people in finding helpful content for lessons, having a support system for problem-solving, and being convenient to use were high. In another part, confirmatory factor analysis confirmed the criteria and items by four factors. Test reliability on 30 students before and after showed that the questionnaire has good reliability in all factors. Convergence validity with the technology acceptance questionnaire showed that there was a direct and positive relationship.Conclusion: The four factors questionnaire, which comprised performance expectations, effort expectations, facilitative situations, and social influence, with feasibility, and usability, can be used as a valid questionnaire in an Iranian population.